The 1961 green and white golden jubilee book - La Salle Brothers-De La Salle University, Manila (Animo Repository, 1961)
The 1961 Green and white golden jubilee book was dedicated to all the La Salle Brothers who have guided the Filipino youth for the last fifty years.